Reaproveitamento de resíduo de mineração na produção de pavers de concreto - Moraes, Radêmora Silva Briano de (Universidade Federal do Tocantins, 2020)
In contemporary times, the need for raw materials and a more sustainable economy has encouraged the study of the feasibility of using waste generated in industry to produce materials useful for civil construction, such as ceramics, concrete and aggregates. Mineral activity generates a significant amount of waste, a material that has the potential to be used in construction, which is a large consumer of raw materials. In view of this, in the characterization of the residue it was found that it has similar particle size to that of a filler. Therefore, the material was dosed in two ways, the first trait type being a mass replacement of the fine aggregate in percentages of 5%, 10% and 20%. The second type of trait was the cement replacement trait in the proportions of 5%, 10% and 20%. Thus, the pavers produced passed the verification of NBR 9781 regarding visual, dimensional evaluation, resistance and absorption. the traits with 5% and 10% percentage of both dosage types met the norm, and the 5% proportioned filler trait showed an increase in resistance and the 20% aggregate replacement trait did not meet the standard due to the workability of the concrete and the difficulty of thickening it.